Case Report: A Rare Case of Metachronous Multiple Primary Lung Cancers in a Patient With Successful Management by Switching From Anti-PD-1 Therapy to Anti-PD-L1 Therapy - Lin, Xinqing; Qiu, Guihuan; Li, Fang; Deng, Haiyi; Qin, Yinyin; Xie, Xiaohong; Jiang, Juhong; Song, Yong; Liu, Ming; Zhou, Chengzhi (Frontiers in Immunology, 2021)
Without global standard diagnostic criteria, distinguishing multiple primary lung cancers (MPLCs) from intrapulmonary metastasis or histologic transformation has been a big challenge in clinical practice. Here, we described a rare case of metachronous adenocarcinoma and small cell lung cancer (SCLC) in a patient who developed drug resistance to pembrolizumab. Both DNA-sequencing and RNA-sequencing were performed on primary adenocarcinoma and resistant lesions. Through the comparison of primary adenocarcinoma and novel lesion mutation profiles, along with bioinformatic estimation of immune proportion by using RNA sequence data, we revealed the origin and tumor microenvironment of the two lesions. No shared mutations were detected between lung adenocarcinoma (LUAD) and SCLC from the same patient, suggesting these two lesions might be from separate primary lung cancers. Compared to LUAD, SCLC showed a relatively cold microenvironment, including negative PD-L1. The patient obtained durable clinical benefits upon treatment with atezolizumab, without experiencing immune-related adverse events. Disease progression should be monitored with prompt re-biopsy and molecular profiling to spot a potential histologic change and to shed light on therapeutic alternatives. The use of atezolizumab, either alone or in combination with other agents, may be a potential therapeutic strategy for patients with both LUAD and SCLC.